EXPLORING HUSBAND-WIFE INTERACTIONS AND CULTURE OF FISHING FAMILIES IN WEST JAVA COASTAL AREAS: Eksplorasi Interaksi Suami-Istri dan Budaya Keluarga pada Keluarga Nelayan di Wilayah Pesisir Jawa Barat - Rizkillah, Risda; Defina, Defina; Hastuti, Dwi; Muflikhati, Istiqlaliyah (Jurnal Ilmu Keluarga dan Konsumen, 2024)
Coastal areas are areas with high extreme poverty with low family interaction. This research explores husband-wife interactions and cultural roles in fishing families in the northern and southern coastal areas. This research used an exploratory study following a mixed methods research approach (concurrent embedded). Husband and wife interactions were measured using a modification of the Chuang instrument. Respondents of survey method consisted of 456 fishermen's wives in West Java, in-depth interviews consisted of 18 husbands and 18 wives, and Focus Group Discussion (FGD) 1 and 2 consisted of 120 people. The research results show that there are no couples in the high category for total husband-wife interaction. The majority of husband-wife interactions in this study were in the low category. Wives in the north region express affection and make decisions for their husbands more often than wives in the south region. On the other hand, wives in the south region are more often angry and annoyed with their husbands than wives in the north region. However, wives in the south region also more often feel safe when their husbands must make essential decisions than wives in the north region. This research implies that the findings can be input for stakeholders to improve the quality of family interactions based on the north and south coastal areas.